Aplikasi pendekatan pemasaran tempat ke atas institusi masjid - Saimi, Bin Bujang (Universiti Malaysia Sarawak (UNIMAS), 2015)
Mosque institutions invite discussion on its weakness of mosque program. Present research or discussion blame the community around the mosque for not participating in the mosque. This thesis explore the mosque in the context of place marketing, using marketing methods for products or services and in line the needs and requirements of users. Marketing place in the context of the mosque institution refers to a strategic effort to improve the competitiveness of the mosque with the way of marketing, promotion and branding of mosque. Two theory, the theory of planned behavior and social exchange theory was used to identify the factors that influence individual attendance to the mosque. Theory of planned behavior explain internal and external factors that influence an individual's behaviour and social exchange theory also relates to the existence of the relationship. A conceptual model that contains a factor of religiosity, family, peer and mosques infrastructure was proposed. Through the interview process with the expert, the four constructs have been identified as factor affecting attendance to the the mosque. The constructs is form the basis for questionnaires. Reliability value through Alpha Cronbanch and test retest analysis are at a very high level and convincing. Construct validity of the questionnaire was assessed using convergent and discriminant analysis and factor analysis. Both the analysis indicate that the questionnaire items are on the high level of consistency and measure what is supposed to measured. The findings of this research have achieved all the objectives of the research and answer the two research questions. This study successfully illustrates the perception and relationships of respondents in Sarawak against the mosques by gender, age, race, education, marital and employment. This thesis identified a positive change of factor for religiosity, family, peer and mosque infrastructure to influence attendance to the mosque. Contribution to theory is combine on marketing concept, the theory of planned behavior and social exchange theory applied to community of Malaysian. This study can assist the religious authorities and the mosque management committee in determining policies relating to mosque program. This thesis the basis for future research on the marketing. Overall, this study successfully describes the behavior of consumers mosque through the factors that affect attendance at the mosque.